Factors Affecting Vietnam's International Economic Integration - Pham, Thanh Thi; Tran, Trang Mai; Nguyen, Hiep Trong (Darul Yasin Al Sys, 2025)
International integration enables countries to cooperate, utilizing shared resources for mutual benefit, and promoting global prosperity. There are three levels of integration: global, regional, and bilateral. Economic integration involves joining organizations, signing trade agreements, and facilitating cross-border flows of goods and capital, enhancing market access and productivity. Technology, trade liberalization, and financial openness are major drivers, with AI as a future growth catalyst. Vietnam's integration has bolstered its economy, increasing GDP and export capacity. However, challenges like competitive pressures, dependency on foreign resources, and regional disparities exist. To navigate these, Vietnam needs policies that balance growth, reduce dependency, and preserve cultural identity, ensuring inclusive and sustainable development.